Sistem Kontrol Gerak Kaki Robot Dengan Memperhatikan Kondisi Suhu Motor Servo Pada Bagian Lutut Robot Humanoid - Aris Prihatin; Akhmad Musafa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
ABSTRACT In this final task is discussed system is designed using an innate Bioloid Type-A robot with 18 servo dynamixel AX-12 A. With the dimensions of the humanoid robot range of arms has a length of 22 cm and a height of 56 cm robot. Each joint is moved by one servo motor. The electronic system consists of a CM-530 controller, AX-12A dynamixel servo motor, temperature sensor on the dynamixel ID13 and ID14 servo motor. In testing the motion of the walking robot does not pay attention to the temperature condition of the servo motor, the robot managed to walk straight with a distance of 180 cm, but at a distance of 180 cm fell with the results of reading serial monitors ID13& 4 = 47°C and 42°C. At a distance of 20 cm, servo temperatures ID13&14 = 32°C and 31°C. At a distance of 40 cm, servo temperatures ID 13 & 14 = 34°C and 32°C. At a distance of 60 cm, servo temperatures ID 13&14 = 37°C and 34°C. At a distance of 80 cm, servo temperatures ID 13&14 = 38°C and 36°C. At a distance of 100 cm, servo temperatures ID 13&14 = 40°C and 37°C. At a distance of 120 cm, servo temperatures ID 13&14 = 41°C and 37°C. At a distance of 140 cm, the temperatures ID 13&14 = 44°C and 40°C. At a distance of 160cm, the temperatures ID 13&14 = 46°C and 41°C. At a distance of 200 cm, temperatures ID 13&14 = 49°C and 44°C. the robot motion test runs by observing the temperature condition of the servo motor, the robot manages to walk straight with a distance of 60 cm, the temperature of the serial monitor reading ID 13 & 14 = 41°C and 47°C, but at a distance of 60 cm the robot turns right toward a distance of 100 cm , servo temperatures ID13&14 = 44°C and 52°C. The robot goes straight back a distance of 100 cm to 200 cm. At a distance of 20 cm the robot runs, servo temperatures ID 13&14 = 37°C and 42°C. At a distance of 40 cm, servo temperatures ID 13&14 = 39°C and 44°C. At a distance of 60 cm, servo temperatures ID 13&14 = 41°C and 47°C. At a distance of 80 cm, with servo temperatures ID 13&14 = 42°C and 49°C. At a distance of 120 cm, servo temperatures ID 13&14 = 44°C and 52°C. At a distance of 140 cm, servo temperatures ID 13&14 = 45°C and 52°C. At a distance of 180 cm, servo temperatures ID 13&14 = 47°C and 54°C. At a distance of 200 cm, servo temperatures ID 13&14 = 48°C and 55°C.